Analysis of Children Health Indicators on the Achievement of Index of Community Health Development in Tanjung Jabung Timur Regency - Dwi Noerjoedianto; Andi Subandi; Andy Amir (Budapest International Research and Critics University, 2021)
The Public Health Development Index (IPKM) is an indicator to determine the level of success in health development in a district. There are several indicators to determine the IPKM value. Child health is the one an indicator of IPKM, has 6 indicators; child malnourished, child stunting, child overweight, child weighing, neonatal visit, and complete immunization. Methodology this was quantitative research. This study was conducted 5 months starting from May to October 2019. The data analyzed used the public health development index formula that has been determined by calculating weights for each indicator and then used minimum and maximum standard values. The results and conclusions were the sub-indicators of the health service group in 2016 amounted to 0.71819347, in 2017 amounted to 0.686645863, in 2018 amounted to 0.730251925, this value was fluctuating in 2016-2018. From 6 sub-indicator of child health, child stunting still has a low value which indicates that this sub-index under adverse condition when compared to the other sub-indicator. However, there are must be improvements to increase this value.